The control of DNA gyrase expression and its role in deletion formation in Salmonella enterica - Keane, Orla Mary (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Microbiology, 2003)
Salmonella typhimurium strain CJD671 can undergo the deletion of a 5kb segment of DNA from its large virulence plasmid. This results in a transcriptional fusion between the rlgA gene, encoding a putative site-specific resolvase, and the spvR virulence gene regulator. The strong activity of the rlgA promoter results in the overexpression of a lacZ reporter gene in the spv locus. Deletions are selected for by lactose and only occur when the bacteria are grown at elevated osmolarity.
Keywords: Microbiology, Ph.D.; Ph.D. Trinity College Dublin